Implementation of an effective cash waqf collection and distribution method in Perlis: a case study of the Perlis Islamic Religion And Malay Council (MAIPs) / Nurnazifa Gzahli ... [et al.] - Gzahli, Nurnazifa (Universiti Teknologi MARA, Perlis, 2024)
Cash waqf is one form of waqf using cash. It plays an important role in generating funds for the country's economic development in terms of education, health, and social welfare. Therefore, the management and administration related to cash waqf need to be emphasised and streamlined for the continuation of its benefits. In relation to that, the aim of this study is to find out the implementation of cash waqf in the State of Perlis, which is implemented by the Council of Islamic Religion and Malay Customs of Perlis (MAIPs) as the sole trustee of waqf property in this state. This study is a qualitative study using the semi-structured interview method. The interviews were conducted with four selected officials at MAIPs. The results of this study found that the methods of collecting cash waqf funds by MAIPs are through payments at waqf counters, waqf funds, salary deductions by government employees, and payments through bank accounts. This study also explains the distribution of cash waqf revenue by MAIPs. Based on the information obtained from the MAIPs officers, it turns out that the implementation of cash waqf has greatly benefited the community. Through the results of this study, it can give insight and spark ideas for the next researcher to carry out further studies on waqf, especially regarding cash waqf, such as the role of cash waqf specifically in sectors of interest in Malaysia.